Pre-service Elementary Teachers’ Mental Model on Heat Transfer Concept as the Effect of Applying CDOI Model Integrated MIKiR Approach - Jeanne Miera Mangangantung; Tommy Tanu Wijaya; Riki Apriyandi Putra; Neni Hermita (AL-ISHLAH: Jurnal Pendidikan, 2021)
The purpose of this study is to strengthen the mental model of prospective elementary school teacher candidates by using the MIKiR (mengalami, interaksi, komunikasi, internalisasi, and refleksi) method, which is directed towards conceptual growth and is based on the MIKiR framework (CDOI Model). The research was carried out utilizing a pre-experimental approach with a pretest-posttest design in one group for this study. The research was carried out on pre-service primary teachers at the Universitas Riau, in Indonesia. The instrument used to collect data was a heat transfer conceptual understanding test (HTCU Test), which consisted of three sections of the question, each of which had previously been verified and evaluated to ensure that the participants were eligible. Using the MIKiR approach (experiencing, interaction, communication, and reflection), this study found that implementing the CDOI model of conceptual development-oriented instruction had a high level of success in enabling the creation of mental models. Furthermore, it can aid in the conceptualization and development of the concept of heat transfer and the formulation and overall knowledge of the concept.